A preliminary study on the changes of fecal short chain fatty acids in patients with traumatic spinal cord injury in the chronic phase - Zhang, Dejian; Peng, Run; Yang, Degang (Spinal cord series and cases, 2025)
Study design Cross-sectional explorative observational study. Setting The China Rehabilitation Research Center is one of the centers for spinal cord injury in China, and this study investigates the Chinese part of spinal cord injury. Objective To observe the changes of fecal short-chain fatty acids (SCFA) in patients with traumatic spinal cord injury (TSCI) compared with normal controls. Methods Thirty-eight patients with TSCI who were hospitalized in Beijing Boai Hospital of China Rehabilitation Research Center from April, 2017 to October, 2018 were recruited. Basic data such as age, gender, neurological level, etiology, and defecation method were recorded, and neurogenic bowel dysfunction score (NBD) was assessed. Twenty-one healthy subjects from the staffs of Beijing Bo’ai Hospital were recruited as the control group. Fresh stool samples were collected and gas chromatography–mass spectrometry (GC-MS) was used to determine the contents of caproic acid, isovaleric acid, isobutyric acid, valeric acid, butyric acid, propionic acid and acetic acid in feces of TSCI patients and controls. The Mann-Whitney U test was used to compare SCFA levels between the two groups. Results Compared with healthy controls, the levels of isovaleric acid and isobutyric acid in the feces of TSCI patients increased, while the levels of butyric acid and acetic acid decreased, and the differences were statistically significant ( P < 0.05). Conclusion The fecal content of propionic acid and butyric acid decreased while that of isobutyric acid and isoamyl acid increased in patients with chronic TSCI.